Washcoating of cordierite honeycomb with vanadia–tungsta–titania mixed oxides for selective catalytic reduction of NO with NH3. Issue 2 (20th November 2014) - Liu, Bo; Du, Jun; Lv, Xiaowei; Qiu, Yue; Tao, Changyuan
Abstract : The application of monolithic coated catalysts to NO x abatement is a crucial issue for practical applications to enhance the mechanical strength, economize the cost, facilitate recycling etc ., compared with the conventional monolithic extrusive catalysts. Abstract : The application of monolithic coated catalysts to NO x abatement is a crucial issue for practical applications to enhance the mechanical strength, economize the cost, facilitate recycling etc ., compared with conventional monolithic extrusive catalysts. In the present work, cordierite honeycomb monoliths coated with V, W and Ti catalyst were synthesized, characterized and tested in the selective catalytic reduction (SCR) of NO with NH3 . The coating process conduced a high dispersion of active species, and generated an enrichment of tungsta and vanadia on the surface of the coating. Raman and UV-Vis DRS spectra confirmed the speciation of vanadia, which was mainly presented in an isolated state with a large proportion of 88.68%; the other oxides were found in the polymeric state possessing one mono–oxo VO terminal band and three bridging V–O–M bands (MV or support cation). XPS indicated the co-existence of pentavalent vanadium and a tiny proportion of tetravalent vanadium. The layer coated onto the cordierite substrate possessed a homogeneous distribution with strong adherence and deep penetration with the catalytic components dipping into cordierite. The coated monolithic catalyst exhibited desirable catalytic performance with the NO removal rate exceeding 90% in the range of 350 to 450 °C, and a strong tolerance to poisoning in sulfur and moisture in the NH3 -SCR reaction.